Elaboração de frozen yogurt com propriedades funcionais - Corte, Fabiane Fagundes Dalla (2008)
The search for the population s better quality of life is attracting the food industry interest in developing products with functional characteristics, offering wholefoods, fortified, enriched or improved food, causing effects potentially beneficial to healthy in the preventive and therapeutic aspects. This work aimed to elaborate a frozen yogurt with functional properties from yogurt supplemented with prebiotic (inulin), calcium caseinate and probiotics. The lactic cultures used were the traditional and the probiotic lactic cultures in three different concentrations (0,5%, 1,0% e 1,5%). The elaboration process of the frozen occurred from the development of the yogurt, in concentrations already mentioned, observing the pH values and, later, through the processes of homogenization of the ingredients, mixing in low temperature (ice cream maker), packing and freezing of the product at a temperature of -22ºC. The carried out physicochemical analyses were for pH, acidity expressed as lactic acid, lactose level, ash level, protein level, fat level and overrun; the microbiological analysis, in a 35-day period of storage and in 7-day intervals, to evaluate the feasibility of the traditional species lactic cultures Streptococcus salivarius ssp. thermophilus, Lactobacillus delbrueckii ssp. Bulgaricus and, probiotics Lactobacillus acidophilus e Bifidobacterium sp. Microbiological analyses of the traditional lactic cultures and liofilized probiotics were carried out for the certification of the number of microorganisms, respectively. Sensorial analysis was carried out in three alternate days, with two days in the UNIFRA (Franciscan University of Santa Maria, RS) Technical and Dietetic Laboratory and the third day in the UFSM (Federal University of Santa Maria, RS) Sensorial Analysis Laboratory with the analyzed features being: color, flavor, smell, consistency and total quality using a structured hedonic scale with 9 scores. The intention of buying the product and its preference were evaluated in this research making 105 non-trained tasters. The experimental data generated through the sensorial analysis results were submitted to variance analysis (ANOVA) and the differences of the means compared through the Tukey. Concentrations of 1.0% and 1.5% of traditional cultures and probiotic had no significant difference in relation to sensory analysis developed. To order the test was used in preference to the table and Newell MacFarlane where the formulation of 0.5% of crops and traditional probiotic milk obtained the lower acceptability.